2008
DOI: 10.1007/s00276-008-0307-8
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of pre- and postpubertal human larynx: a cadaver study

Abstract: This study investigates the differences in proportion and structure of the larynx in both children and adults, as well as changes which the larynx undergoes during puberty and adolescence. Furthermore, we have tried to answer the question on the existence of laryngeal sexual dismorphism in pre-pubertal (or pubertal) children. Larynges of 20 adults (10 men and 10 women) and 34 larynges of children not more than 12 years of age were acquired from the Forensic Medicine Department of the Medical University of Wars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 28 publications
4
37
1
3
Order By: Relevance
“…Ainda que pouco estudadas em mamíferos, caracterís-ticas de dimorfismo sexual na laringe são reconhecidas em seres humanos (Maue & Dickson 1971, Wysocki et al 2008a, bovinos (Wysocki et al 2008b) e renas (Frey et al 2007), embora não encontradas em cães domésticos (Tayama et al 2001), equinos (Charuta et al 2009) nem suínos (Wysocki et al 2010). De acordo com Harrison (1995) na maioria das espécies a laringe dos machos seria maior que a das fêmeas e isto decorreria de um porte corporal maior, mas também de uma alta afinidade de receptores de andrógenos nas cartilagens laríngeas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Ainda que pouco estudadas em mamíferos, caracterís-ticas de dimorfismo sexual na laringe são reconhecidas em seres humanos (Maue & Dickson 1971, Wysocki et al 2008a, bovinos (Wysocki et al 2008b) e renas (Frey et al 2007), embora não encontradas em cães domésticos (Tayama et al 2001), equinos (Charuta et al 2009) nem suínos (Wysocki et al 2010). De acordo com Harrison (1995) na maioria das espécies a laringe dos machos seria maior que a das fêmeas e isto decorreria de um porte corporal maior, mas também de uma alta afinidade de receptores de andrógenos nas cartilagens laríngeas.…”
Section: Discussionunclassified
“…As medidas bilaterais (1e, 1f, 1g, 2f, 2g, 3a, 3b e 3c) foram realizadas em ambos os antímeros e obtida uma média. As 23 medidas foram adaptadas dos trabalhos de Wysocki et al (2008a), Wysocki et al (2008b), Charuta et al (2009) e Wysocki et al (2010 e encontram-se listadas no Quadro 1 e esquematizadas na Figura 1. Além das dezesseis laringes mensuradas, outra laringe pertencente a um espécime fêmea foi submetida à dissecação e desarticulação das cartilagens para fotomacrografias individualizadas.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…This predominance has yet to be explained; however, gender differences in larynx size/growth and consequently higher "Bernoulli forces" in females for a given respiratory demand could be a contributing factor [5]. Thus, an inherited disorder affecting laryngeal growth could also explain why the condition usually presents in adolescence [12,13]. A recent study by Hilland and colleagues [14] describing an association between congenital laryngomalacia and (mainly supraglottic) laryngeal closure in adolescence, points out a likely predisposition for supraglottic exercise-induced laryngeal obstruction (EILO), whereas case studies have demonstrated that congenital laryngomalacia can be inherited [15,16].…”
mentioning
confidence: 99%
“…This model would be the simplest explanation for the findings and the established gender difference. The influence of gender is a well-known phenomenon in autosomal dominant traits, for example, pre-senile baldness in which hormonal differences play a role in the expression of the trait [13]. Unknown, but similar mechanisms could be the reason for the female predominance in supraglottic EILO [15,16].…”
mentioning
confidence: 99%